High-Resolution Cryogenic Spectroscopy of Single Molecules in Nanoprinted Crystals - Musavinezhad, Mohammad; Renger, Jan; Zirkelbach, Johannes; Utikal, Tobias; Hail, Claudio U.; Basché, Thomas; Poulikakos, Dimos; Götzinger, Stephan; Sandoghdar, Vahid (ACS nano, 2024)
We perform laser spectroscopy at liquid helium temperatures (T = 2 K) to investigate single dibenzoterrylene (DBT) molecules doped in anthracene crystals of nanoscopic height fabricated by electrohydrodynamic dripping. Using high-resolution fluorescence excitation spectroscopy, we show that zero-phonon lines of single molecules in printed nanocrystals are nearly as narrow as the Fourier-limited transitions observed for the same guest-host system in the bulk. Moreover, the spectral instabilities are comparable to or less than one line width. By recording super-resolution images of DBT molecules and varying the polarization of the excitation beam, we determine the dimensions of the printed crystals and the orientation of the crystals’ axes. Electrohydrodynamic printing of organic nano- and microcrystals is of interest for a series of applications, where controlled positioning of quantum emitters with narrow optical transitions is desirable.
CRIS-Team Scopus Importer:2024-07-26
Keywords: nanocrystal; nanoprinting; quantum emitter; single molecule; single-photon source; spectroscopy